ЛАКУНАРНОСТЬ СОЦИОКУЛЬТУРНОЙ ТРАДИЦИИ ВЫРАЖЕНИЯ МЕСТОИМЕНИЙ «Я» И «МЫ» В АНГЛИЙСКОМ И РУССКОМ ЯЗЫКАХ - Жумамуратова, Р. (SCIENCE and SOCIETY, 2016)
The article deals with the issues of using the personal pronoun «I» in some foreign languages. The author of the article studies the siciocultural traditions of expressing the pronouns «I» and «we» in different languages.